2018
DOI: 10.1111/cas.13695
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition synergizes with calcium mobilization to achieve efficient therapy of malignant gliomas

Abstract: Autophagy plays a critical role in tumorigenesis, but how autophagy contributes to cancer cells’ responses to chemotherapeutics remains controversial. To investigate the roles of autophagy in malignant gliomas, we used CRISPR/CAS9 to knock out the ATG5 gene, which is essential for autophagosome formation, in tumor cells derived from patients with glioblastoma. While ATG5 disruption inhibited autophagy, it did not change the phenotypes of glioma cells and did not alter their sensitivity to temozolomide, an agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Ca 2+ is not only involved in the regulation of Erk1/2 signaling but is also involved in the regulation of AKT and STAT3 signaling [62,63]. Ca 2+ also plays an important role in regulating autophagy [64,65] and epithelial-mesenchymal transition (EMT) [63], both of which are related to drug resistance to TKIs [28,66]. As a result, blocking Ca 2+ signaling may be a promising strategy that enhances the clinical efficacy of TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ is not only involved in the regulation of Erk1/2 signaling but is also involved in the regulation of AKT and STAT3 signaling [62,63]. Ca 2+ also plays an important role in regulating autophagy [64,65] and epithelial-mesenchymal transition (EMT) [63], both of which are related to drug resistance to TKIs [28,66]. As a result, blocking Ca 2+ signaling may be a promising strategy that enhances the clinical efficacy of TKIs.…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown inhibition of autophagy induction by CRISPR-Cas9-mediated ATG5 gene knockout in TGS01 and TGS04 cells in conjunction with a calcium mobilization agent (nigericin) that works together to increase mitochondrial reactive oxygen species for cell death [ 55 ]. Another study showed that CRISPR-Cas9 mediated knockout of TSC2 (Tuberous Sclerosis 2) gene, an autophagy promoting molecule, in GBM LN18 cells rendering them to be more susceptible to cell death in response to photodynamic therapy (PDT) [ 56 ].…”
Section: Application Of Crispr-cas9 To Identifying Genetic Regulators Of Autophagy In Gbmmentioning
confidence: 99%
“…Autophagy inhibition potentiates NIG treatment. In a recent study Vu et al demonstrated a reduction in spheroid formation by ATG5 deficient glioma cells on treatment with NIG [ 138 ].…”
Section: Ionophoresmentioning
confidence: 99%